Improving Fellows' Presentations at Case-Conference: A Quality Improvement Initiative. (4th October 2017) - Kanwar, Anubhav; Perez, Federico; Donskey, Curtis
Abstract: Background: Case-conferences are a time-honored tradition in fellowship training programs. Despite the major role that they play in imparting medical knowledge and teaching the art of communication, there is limited information on how to improve the quality of case-conference presentations. Methods: To assess the quality of case-conferences, we surveyed faculty in Division of Infectious Diseases at Case Western Reserve University School of Medicine. The survey consisted of 14 questions on a Likert scale assessing fellows' case presentations and discussion, presentation style, audience participation, and willingness to review fellows' presentations. Based on the initial survey findings, case-based demonstrations were used to encourage participation, focus and clarity. Individualized feedback was given to fellows before and after their presentations. A follow-up survey was conducted 9 months after the intervention. Results: Twenty-two participants completed the initial survey and 19 completed the follow-up survey. The table provides a comparison of the responses to the surveys before and after the intervention. On the follow-up survey, 72% participants indicated that case-conferences improved, while 28% felt there was no change. Conclusion: An intervention based on input from faculty resulted in improvement in the quality of case-conference presentations by Infectious Diseases fellows and encouraged faculty participation. Table. Quality indicators for case-conference from initial and follow-up survey Disclosures: All authors: No reported disclosures.